Targeted gene therapy in radiotherapy - Kamenšek, Urška (Radiology and oncology (Ljubljana), 2008)
The dramatic pace in development of gene therapy over the past decades has made it a realistic alternative for the treatment of cancer. Radiotherapy, on the other hand, is one of the most commonly used and well established cancer treatment modalities. The latest improvements in the physical targeting ability of radiotherapy and understanding of the molecular mechanism involved in the cellular response to ionizing radiation have presented an opportunity to combine radiotherapy with gene therapy. This review article will focus on gene therapy strategies that can be used to enhance the effectiveness of radiotherapy, with an emphasis on transcriptional targeting approaches.
Keywords: Gene therapy; genska terapija; onkologija; radioterapija; Radiotherapy